Drug eluting balloon angioplasty for assisted maturation of failing fistulae. Issue 2 (March 2018) - Mallios, Alexandros; Hull, Jeffrey; Boura, Benoit; Costanzo, Alessandro; Combes, Myriam
Objective: To present our experience of balloon-assisted maturation with drug-eluting balloon dilation in patients with recurrent failing arteriovenous fistulae. Case series: Three patients (all males, mean age 71 years) with a complex history of failed attempts at native fistula creation underwent surgical creation of arteriovenous fistulae. Two patients had a two-stage brachio-brachial fistula and 1 had a brachio-cephalic fistula that also required subsequent elevation. After a few weeks of preserved patency with a thrill detected clinically, all patients had a gradual deterioration of flow manifested with loss of thrill and multiple severely stenotic lesions of neo-intimal hyperplasia seen on duplex ultrasound. All 3 non-maturing native arteriovenous fistulae had 1 or more angioplasties with regular balloons that were initially successful; however, they rapidly deteriorated with a loss of thrill and a recurrence of multiple stenosis. Drug-eluting balloon dilation was used subsequently as a last resort to save these failing fistulae. All procedures were successful with the preservation of patency and adequate fistula flow (>600 mL/min) during the follow-up period (4-8 months, mean 6 months), and all patients received successful dialysis with 2-needle cannulation of their fistulae. There were no adverse events during the study period. Conclusions: Drug-eluting balloon angioplasty was to salvage nonmaturing fistulae with durable results in complex patients where conventional treatment had previously failed. Drug-eluting balloons may provide a useful treatment option for patients prone to multiple access failures due accelerated neo-intimal hyperplasia.